Application of Set Theory for Optimization of Business Processes in Secondary Special Education Institutions - N. I. Listopad; E. A. Bushchyk (Цифровая трансформация)
The article examines the role of interoperability as a key element of the digital transformation of education. Three levels of interoperability are identified: organizational, semantic and technical, each of which plays an important role in ensuring effective data exchange and integration of business processes. Particular attention is paid to the organizational level, where optimization of business processes is critical to improving the quality of education. Set theory is used as a tool for optimizing business processes, which allows formalizing data and identifying patterns, which contributes to deeper analysis and informed decision-making. Based on the analysis of internal documents of educational institutions, a business process diagram has been developed that reflects the activities of training specialists of secondary specialized education institutions. This substantiates the importance of integrating management, operational and supporting business processes to achieve high-quality results in the educational sphere.